Development of Teaching Modules for Strategic Management Courses Based on Problem-Based Learning to Increase Students' Cognitive Flexibility - Ahmad Saeroji; Muhsin; Aulia Prima Kharismaputra (Economics Education Department Universitas Negeri Semarang, 2024)
This research aims to develop and test whether the problem-based learning (PBL) teaching module that the author created in the strategic management course can increase students' cognitive flexibility. The research method used is Research and Development (R&D) with the ADDIE model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The sample in this study was students of the Office Administration Education Study Program, Semarang State University, class of 2021, with 109 students divided into three classes. Furthermore, the results of the module that has been developed are tested regarding the increase in the average cognitive flexibility score after carrying out the pre-test and post-test. Based on research results, the experimental class that used the PBL module showed an average increase in cognitive flexibility score of 17.3 points, while the control class only increased by 4.4 points. Statistical tests showed a significant increase in the experimental class (p < 0.001), while the control class did not show a significant increase (p = 0.065). Meanwhile, student activities in the experimental class showed active participation in the learning process, problem-solving involvement, and better teamwork than in the control class. Student feedback indicates that PBL makes learning more enjoyable, helps students think critically, and is relevant to the real world.